Comparing the Survivability of Lactobacillus Species in Various Probiotic Delivery Vehicles. (29th September 2016) - Fleming, Derek; Kesey, Jennifer; Rumbaugh, Kendra; Dissanaike, Sharmila
Abstract : Background: Probiotics are widely used in healthy and nonhealthy individuals to maintain a favorable gut microbiome and inhibit pathogen takeover. Currently, there are many varieties of probiotic delivery vehicles on the market, with no real research indicating which is the most effective at allowing for colon colonization. In this study, we sought to determine if probiotic preparation influences the ability of Lactobacillus species, one of the most common genera of probiotic bacteria, to survive gastric acidity. Objective : To determine the survivability of lactobacilli in stomach‐level acidity for a variety of probiotic delivery vehicles. Materials and Methods : We tested the ability of 6 different probiotic preparations—enterically encapsulated pills, nonencapsulated pills, lyophilized powder, yogurt, yogurt drink, and kefir—to enhance survivability of lactobacilli in pH 2.0–adjusted phosphate‐buffered saline over time. Colony‐forming units were enumerated by spot plating on both nonselective (brain‐heart infusion) and selective (Rogosa SL) agar. Results : Regardless of delivery vehicle, lactobacilli are very capable of surviving gastric acidity, allowing for passage into the intestines.